Dynamic mechanical analysis to assess viscoelasticity of liver tissue in a rat model of nonalcoholic fatty liver disease. (June 2017) - Zhang, Xinyu; Gao, Xuehua; Zhang, Pengpeng; Guo, Yanrong; Lin, Haoming; Diao, Xianfen; Liu, Yingxia; Dong, Changfeng; Hu, Yaxin; Chen, Siping; Chen, Xin
Highlights: Our hypothesis is that the mechanical properties of liver tissue are affected by the increase of fat accumulation in liver tissue, which results in changes in its physical microstructure and chemical contents. We performed a dynamic mechanical analysis (DMA) test to assess the viscoelasticity of liver tissue in low frequency range in a rat model of NAFLD. The results showed significant changes ( p  < 0.05) in storage modulus in livers with moderate to severe (S2 to S4) steatosis in comparison with livers without steatosis (S0), while the loss modulus demonstrated significant changes earlier in stage S1, indicating that fat accumulation affects the mechanical properties of liver, particularly viscosity. These results also suggest that mild inflammation may affect the mechanical properties, which requires further verification. Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common liver disorder in both developed and developing countries. A noninvasive method of detecting early stage NAFLD and distinguishing non-alcoholic steatohepatitis (NASH) from simple steatosis (SS) would be useful. The over-accumulation of fat in hepatocytes alters the physical microstructure and chemical contents of the liver tissue. This study included dynamic mechanical analysis (DMA) testing on liver samples from a rat model of NAFLD to determine whether the tissue shows any significant changes in viscoelasticity due to the histological changes. Liver steatosis was induced in 57 rats by gavage feeding of a high fat emulsion; 12 rats received a standard diet only and served as controls. Each rat provided 2 or 3 samples for DMA tests. The shear modulus and loss modulus were measured at 9 frequency points evenly-spaced in the range from 1 Hz to 41 Hz. The phase velocity of shear wave was calculated from the measured modulus. Multivariate T 2 test was used to assess the significance of intra-group difference. The results showed significant changes ( p  < 0.05) in storage modulus in livers with moderate to severe (S2 to S4) steatosis in comparison with livers without steatosis (S0), while the loss modulus demonstrated significant changes earlier in stage S1, indicating that fat accumulation affects the mechanical properties of liver, particularly viscosity. However, no significant differences were observed between the steatosis grades. These results also suggest that mild inflammation may affect the mechanical properties, which requires further verification. These findings provide new information about the mechanical properties of livers with NAFLD in low frequency range and suggest that it is possible to distinguish normal livers from livers with NAFLD.